The Psychological Conflict of Jefferson in A Lesson Before Dying by Ernest J. Gaines - Irawan, Nico; Kurnia, Fabiola Dharmawati; Mustofa, Ali (Jurnal Bahasa Inggris, 2019)
This research is to analyze Jefferson’s psychological conflict. It talks about a black teenager who lives in America as a victim of the racist ideology at that time and he gets the death sentence because he is accused of murdering the storekeeper. He gets the judgment unfairly and automatically suffers his psychology until he has no hope to live again. This research question is related to psychological conflict and emotions based on the evidence. We took the review of related literature about psychological conflict, emotions, speech acts, communicative language teaching, language and thought. We used qualitative method to analyze the story of Jefferson. This research is useful for education literacy to know more value of Jefferson.